In vivo evaluation of a breast‐specific magnetic resonance guided focused ultrasound system in a goat udder model. Issue 7 (17th June 2013) - Payne, A.; Todd, N.; Minalga, E.; Wang, Y.; Diakite, M.; Hadley, R.; Merrill, R.; Factor, R.; Neumayer, L.; Parker, D. L.
Abstract : Purpose: : This work further evaluates the functionality, efficacy, and safety of a new breast‐specific magnetic resonance guided high intensity focused ultrasound (MRgFUS) system in an in vivo goat udder model. Methods: : Eight female goats underwent an MRgFUS ablation procedure using the breast‐specific MRgFUS system. Tissue classification was achieved through the 3D magnetic resonance imaging (MRI) acquisition of several contrasts (T1w, T2w, PDw, 3‐point Dixon). The MRgFUS treatment was performed with a grid trajectory executed in one or two planes within the glandular tissue of the goat udder. Temperature was monitored using a 3D proton resonance frequency (PRF) MRI technique. Delayed contrast enhanced‐MR images were acquired immediately and 14 days post MRgFUS treatment. A localized tissue excision was performed in one animal and histological analysis was performed. Animals were available for adoption at the conclusion of the study. Results: : The breast‐specific MRgFUS system was able to ablate regions ranging in size from 0.4 to 3.6 cm 3 in the goat udder model. Tissue damage was confirmed through the correlation of thermal dose measurements obtained with realtime 3D MR thermometry to delayed contrast enhanced‐MR images immediately after the treatment and 14 days postablation. In general, lesions were longer in the ultrasound propagation direction, which is consistent with the dimensions of the ultrasound focal spot. Thermal dose volumes had better agreement with nonenhancing areas of the DCE‐MRI images obtained 14 days after the MRgFUS treatment. Conclusions: : The system was able to successfully ablate lesions up to 3.6 cm 3 . The thermal dose volume was found to correlate better with the 14‐day postablation nonenhancing delayed contrast enhanced‐MR image volumes. While the goat udder is not an ideal model for the human breast, this study has proven the feasibility of using this system on a wide variety of udder shapes and sizes, demonstrating the flexibility that would be required in order to treat human subjects.